Learning-by-mediating. Reflexive mediation in action - Bracco, Fabrizio; Gattiglia, Nora; Greggio, Gabriele; Morelli, Mara (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This paper aims at sharing some reflections and results concerning some experiences carried out within a European interdisciplinary Erasmus+ project. The main themes are community and peer mediation, considered from the perspective of educational innovation and experimentation. Two on-line videorecorded meetings of the project are analysed to show that the process of the project and this article-writing was consistent with mediation, that emerges as a topic within a discipline, but also as a cross- disciplinary methodology. The collective construction of meaning becomes a way to acquire knowledge, skills and attitudes while the participants are involved within interactive and constructive educational dynamics.